3D printable lightweight cementitious composites with incorporated waste glass aggregates and expanded microspheres – Rheological, thermal and mechanical properties. (December 2021) - Cuevas, Karla; Chougan, Mehdi; Martin, Falk; Ghaffar, Seyed Hamidreza; Stephan, Dietmar; Sikora, Pawel
Abstract: One of the fields in the construction industry where 3D printing of cementitious composites can play a significant role is associated with manufacturing of lightweight structures. Thanks to 3D printing, structural self-weight can be reduced by topology optimization of printed elements. Moreover, further decrements of self-weight and improvement of thermal insulating properties can be achieved by the mixture design and introduction of materials of low thermal conductivity. To date, limited knowledge on lightweight printable mixtures is available. The main objective of this study is to develop 3D printed lightweight concrete (3DPLWC) mixture, with the intention of replacing natural aggregate with waste glass (WG) by 50 vol.-% and 100 vol.-%. Moreover, expanded thermoplastic microspheres (ETM) were incorporated into the mixture. This led to a reduction in density of the mixtures as well as the thermal conductivity by up to 40%. Comprehensive evaluation of material's fresh properties revealed that the addition of ETM results in 3D printable material with lower yield shear stress and higher plastic viscosity by 28% and 66%, respectively, compared to the mixes without ETM. Moreover, improvement of shape retention, flowability, setting times, and early-hardened mixtures' properties was observed. The mechanical properties of 3DPLWC showed that the replacement of natural aggregate by 50 vol.-% WG led to enhanced flexural and compressive strength of the composite, while full replacement resulted in retaining or slight reduction of the mechanical properties. Highlights: 3DPLWC contained waste glass (WG) and expanded thermoplastic microspheres (ETM). Replacement of aggregate with WG and ETM decreased thermal conductivity by 40%. The inclusion of ETM results in lowering the yield shear stress and increasing the plastic viscosity. Addition of ETM results in remarkable density and mechanical strength reduction of 3DPLWC. Basalt aggregate can be successfully replaced with waste glass up to 50 vol.-% without strength deterioration.